Clinical and diagnostic study of ovine chronic progressive pneumonia (Maedi-Visna) in sheep of Basrah, Iraq - Kamal M. AlSaad; Ali J. Lafta; Mohand H. Lafta; Jihad A. Ahmed (Iraqi Journal of Veterinary Sciences)
In the current study 135 blood samples from local breed sheep (3-5 years old) and of both sexes, raised in Basrah, Iraq, was collected. The suspected animals showed signs of chronic pneumonia, anorexia, emaciation, progressive emaciation, and chronic cough. 25 samples clinically healthy local breeds were served as a control group. 88 sheep were found positive for the specific IgG of Lentivirus with an infection rate 65.18% which was confirmed by the indirect ELISA test. Hematological analysis indicated a significant increase in ESR with significant leukocytopenia, lymphocytopenia, and monocytopenia, with clear differences in indices of clotting factors. On post-mortem examinations, (40) dead carcasses show signs of progressive pneumonia, with an enlarged and heavy lung. Diseased lungs show whitish nodules on the parietal surface. Moreover, Variable whitish patches on the parietal surface of the affected lung were also detected. The histopathological appearance shows lobar pneumonia consists of progressive inflammatory exudation filling the lobar alveolar spaces with severe infiltration of inflammatory cells and erythrocytes inside alveolar spaces. A progressive inflammatory exudation filling the lobar alveolar spaces of the lung consists of inflammatory cell infiltration and exudation with erythrocytes inside the alveolar spaces; also, there is a hyperplastic proliferation of the bronchial epithelial lining was also indicated. Moreover, Early fiberoptic lesion refers to the stage of red hepatization of pneumonia besides many inflammatory cells, and erythrocyte infiltration in the alveolar spaces was also recognized. The disease was confirmed in Basrah, Iraq. Therefore, preventive measures to protect animals in the area is advised.